A Research Agenda for Competency-Based Education - DeBacker, Diane; Kingston, Neal; Mason, Jessica; Parsons, Kelle; Patelis, Thanos; Specht-Boardman, Ryan (Competency-Based Education Research Journal, 2024)
This paper presents an agenda to guide, coordinate, and promote empirical research on competency-based education programs across educational sectors in the United States. Competency-based education (CBE) is an outcomes-based approach to education, where curricula are designed around competencies, and learners’ progression is based solely on their performance-based demonstration of the competencies, not the amount of time they spend on the materials. CBE has the potential to address and resolve long-standing enduring challenges in education. This agenda, developed by experts in research on and the practice of competency-based education, is intended to encourage and inspire researchers with various perspectives and voices to under-take research suggested, encourage rigorous efficacy research, and provide ideas and sample research questions for scholarship. The publication of this agenda coincides with the launch of the new Competency-Based Education Research Journal (CBERJ). There is a significant demand for empirical evidence on CBE’s efficacy, and existing literature reviews have shown that the current state of the research on CBE has gaps. The research agenda is organized in a four-part framework: (1) conceptualization research, (2) design research, (3) implementation research, and (4) efficacy and efficiency research. Undergirding those areas is a cross-cutting set of questions that transcend individual thematic areas. Each part of the agenda’s framework presents sample research questions and sub-topics. This comprehensive (but not exhaustive) research agenda will aid researchers in contributing to the maturing body of evidence on CBE.